O estado da arte sobre o mercado de consumo para terceira idade no Brasil - Michelin, Ana Gabriela Sturzenegger (2017)
The aging population is growing, living longer, having new habits and attitudes, in addition to new wishes and needs, and significantly contributing to the country's national income and, as a result, becomes appealing to the consumer market. Businesses in Brazil hardly carry out projects in this segment, with almost nonexistent information-gathering and market research. Given this scenario, the main objective of this work was to learn about the State of the Art on the consumer market and seniors in Brazil, from 2006 to 2016, in order to verify what kind of academic knowledge we have, as well as the gaps and opportunities on this topic. For methodology, we opted for State-of-the-Art research of a bibliographic and exploratory nature, with content analysis. We analyzed 98 academic papers containing words related to the consumer market (service, product, consumption, marketing and market) and to the elderly (senior, aging, old and elderly). The outcome was: 1) high female participation (71 out of the 98 papers), especially regarding topics that deal with the understanding of the elderly consumer, the construction and reproduction of the elderly’s image, besides the care required at this stage. Lower male participation (27 out of the 98 papers) mainly related to topics that address practical solutions for improvements and adaptations to aging-related issues; 2) geographical mapping of study concentration on the subject, such as SP (40 papers), RS (15 papers), RJ (11 papers) and SC (7 papers); 3) presentation of 9 topics on the study’s papers, as follows: increased demand, services, new technologies, product development, product usage, advertising, media, rights, and Retail/ POS; and 5) indication of trends related to data that show us a growing interest in the subject, whether in the number of papers, in the diversity of geographic areas and educational institutions, and in the topics of the papers. The conclusion is that knowledge about the growing aging population, its reasons and consequences are already quite widespread in the academic field, with many possibilities and need for studies that deepen the knowledge on the elderly consumer, as well as current demands and new solutions for products and services that best meet their needs. The duality of the speech that reinforces stereotypes of the dependent, fragile elderly, or of the active, young elderly responds to a market framework on this segment’s power of consumption, but does not cater to the multiplicity of elderly consumers, making room for new discussions and possibilities of being old. Finally, it is also possible for businesses to consider this segment of individuals over 60 years old in their plans and projects, starting by including them in the market research studies they conduct